2005
DOI: 10.1007/s11104-004-1522-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Azotobacter and Azospirillum strains from the sugarcane rhizosphere

Abstract: Bacteria with the ability to grow on nitrogen-free media and with nitrogenase activity under aerobic or microaerobic conditions were isolated from sugarcane roots collected from four different agricultural locations in Granada (Spain). Isolates were Gram negative rods and were identified as Azotobacter chroococcum and Azospirillum brasilense. Our results suggest that Azotobacter isolates do not have a particular affinity for sugarcane rhizospheres and that, on the contrary, Azospirillum isolates show specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 47 publications
5
58
1
16
Order By: Relevance
“…In comparing the correlation between TNA and SNA of Azospirillum lipoferum, it revealed that they had correlation which was higher than that of the correlation between TNA and RNA. This differed from Tejera (2005) who found that azospirillum had high correlation in the root area and root surface of sugar cane. No other microbes were found at the surface and inside the root of sugar cane in Spain.…”
Section: Azotobacter Chroococcumcontrasting
confidence: 86%
See 1 more Smart Citation
“…In comparing the correlation between TNA and SNA of Azospirillum lipoferum, it revealed that they had correlation which was higher than that of the correlation between TNA and RNA. This differed from Tejera (2005) who found that azospirillum had high correlation in the root area and root surface of sugar cane. No other microbes were found at the surface and inside the root of sugar cane in Spain.…”
Section: Azotobacter Chroococcumcontrasting
confidence: 86%
“…It can enter root, consume surrounding organic substance, fix N 2 and release into the surrounding soil (Steenhoudt & Vanderleyden, 2000). From the study of Tejera (2005), it was found that azotobacter whose species are selected from soil (60%) and root (40%) revealed no close correlation, particularly in the area of fibrous root. No azotobacter was found inside the root of maize in the studying zone because most of azotobacter live freely and prevail in the soil at the appropriate temperature of 30…”
Section: The Effect Of Azotobacter Chroococcum and Azospirillum Lipofmentioning
confidence: 99%
“…In general, variation and distribution of microorganisms is a reflection of soil fertility. As nitrogen is an essential element for plants, nitrogen-fixing bacteria would therefore provide molecular nitrogen for plant use [6]. Azotobacter species belong to the Gram-negative and the polymorphic family of Azotobacteraceae capable of forming capsule and microcyst [7].…”
mentioning
confidence: 99%
“…The colony characters such as colony-margin, size, colour and consistency also differed among the different species of Azotobacter spp. (Tejera, et al 2005;Ahmad, et al 2008). The agronomic importance of Azotobacter spps is due to its the capability of biological nitrogen fixation, synthesis of antibiotics, plant growth hormones (Pandey et al, 1998), vitamins, exopolysaccharides and pigment (Jimenez et al, 2011) and also its antifungal activity (Sudhir et al, 1983).…”
Section: Characteristic Features Of Azotobacter Chroococcummentioning
confidence: 99%